2019
DOI: 10.1002/jper.19-0063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega‐3 fatty acids and aspirin on Porphyromonas gingivalis‐induced periodontitis in rats

Abstract: Background Periodontitis is a common chronic inflammatory disease caused by bacteria which can result in periodontal tissue inflammation, as well as alveolar bone resorption. The purpose of this study was to evaluate the effects of omega‐3 fatty acids plus aspirin (ASA) on ligature‐induced periodontitis in rats. Methods Ninety‐six male Sprague‐Dawley (SD) rats (age 6 weeks) were randomly divided into eight groups (n = 12 each) and had ligatures placed for 7 days, followed by daily treatment with specific drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…It has also demonstrated that, during CHD, upregulated suPAR, nitric oxide (NO), and hs‐CRP were associated with endothelial dysfunction increased risk of CHD 17,18,21 . In this regard, it has been hypothesized that conditions such as periodontitis and CHD may determine the increased release at the serum and salivary levels of IL‐1, IL‐6, prostaglandins, metalloproteases, NO, and hs‐CRP 19 which, in turn, negatively influences the tone of the endothelial wall and, finally, causes a high risk of endothelial dysfunction and CHD development 20,21,22 . For these reasons, there is an increased interest in analyzing the effects of periodontitis as a subclinical increased risk of endothelial dysfunction and CHD 21,23,24,25 …”
Section: Introductionmentioning
confidence: 99%
“…It has also demonstrated that, during CHD, upregulated suPAR, nitric oxide (NO), and hs‐CRP were associated with endothelial dysfunction increased risk of CHD 17,18,21 . In this regard, it has been hypothesized that conditions such as periodontitis and CHD may determine the increased release at the serum and salivary levels of IL‐1, IL‐6, prostaglandins, metalloproteases, NO, and hs‐CRP 19 which, in turn, negatively influences the tone of the endothelial wall and, finally, causes a high risk of endothelial dysfunction and CHD development 20,21,22 . For these reasons, there is an increased interest in analyzing the effects of periodontitis as a subclinical increased risk of endothelial dysfunction and CHD 21,23,24,25 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Recently, omega 3 and/or aspirin was exhibited to be effective reducing ABL by modulating osteoclastogenesis. 31 Furthermore, fish oil diet was shown to decrease ABL in hypercholesterolemic rats with ligature-induced periodontitis. 41 B. lactis administration significantly decreased CAL and ABL in an experimental periodontitis study.…”
Section: Discussionmentioning
confidence: 99%
“…32 In a recent study, omega 3 and/or aspirin decreased iNOS protein synthesis in LPS-stimulated cells. 31 Similarly, Lactobacillus brevis (L. brevis) inhibited iNOS activity which was induced by LPS. 33 Treatment with Weissella cibaria also reduced NO and iNOS expressions together with mRNA levels of iNOS in LPS-induced cells, indicating that probiotic administration was able to inhibit NO by suppressing iNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral and periodontal conditions have an impact on overall health and disease [3]. Bacteria from the mouth can cause infection in other parts of the body when the immune system has been compromised by disease or medical treatments (e.g., infective endocarditis) [4][5][6]. Systemic conditions and their treatment are also known to impact on oral health (e.g., reduced saliva flow, altered balance of oral microorganisms) [7,8].…”
Section: Introductionmentioning
confidence: 99%